Exposure to volcanic ash produced by the Turrialba volcano and respiratory diseases, Costa Rica, 2016 - Vargas-Alfaro, Maite; Douglas-Gordon, Sharline; Chamizo-Garcia, Horacio (Horizonte Sanitario, 2023)
Objective: describe the spatial behavior of contamination by volcanic ash and the effect on the incidence of acute and chronic respiratory diseases in communities exposed to the ash produced by the activity of the Turrialba Volcano during the year 2016. Materials and methods: an ecological, observational, retrospective, cross-sectional and correlational study was carried out, where 36 cantons within 50 km of the Turrialba volcano were categorized, according to their level of contamination. Results: a differentiated behavior is verified in the geographical space affected by the volcanic ash plume, all the territories included in the study resulted in some level of contamination, however three zones are distinguished, high, medium and low contamination. 46.6% of the epidemiological events studied have a higher risk of occurring in cantons with high contamination, over cantons with medium and low contamination. Conclusions: it is possible that the contamination due to volcanic ash has increased the risk of exacerbation of chronic respiratory diseases in the area under the direct influence of the volcanic ash plume. Keywords: Volcanic Ash; Respiratory Tract Diseases; Volcanic Eruptions.